Family agriculture in the city of Teófilo Otoni: Importance and challenges for production in the rural environment (Research, Society and Development, 2020)
Family farming is a way of producing, and in the current national context is as a strategic segment for the production of chemical raw materials, as well as an important role in maintaining the country's food and nutritional security and has been discussed in within the academy, in government policies and social movements. That said, this study aimed to identify as difficulties and the main challenges that family farming faces to produce and maintain itself in rural áreas in the municipality of Teófilo Otoni - MG. To do so, it mas performed a descriptive and exploratory literature search. From this, it appears that there are several difficulties faced by family members, and the lack of technical assistance is undoubtedly one of the main limiting factors. The low capacity of agencies that help, or can help family farmers to develop more complete projects adapted to local conditions, with more detailed statistics on more viable plant and animal species for each farmer. In view of this, we conclude that the development of policies that are more consistent and contextualized with the local reality, emerges as a key element to assist in the sustainable regional development and the valorization of family agriculture.